Clinical evaluation of demineralization and remineralization of intact root surface lesions in the clinic by a quantitative light-induced fluorescence system - TAĞTEKİN, DİLEK; YANIKOĞLU, FUNDA (SPRINGER LONDON LTD, 2012)
Detection of demineralization of root surface caries is an important issue since preventive approaches prolong tooth life. Quantitative light-induced fluorescence (QLF) has been shown to be useful for the laboratory assessment of demineralization of root surfaces. The aim of this study was to determine the demineralization and remineralization of root surface intact and cavitated caries lesions using a QLF system as a nondestructive in vivo method. Noncavitated and demineralized root surface lesions were detected and scored using the QLF system. Oral hygiene education was given and periodontal cleaning was completed before the remineralization treatment. After obtaining baseline QLF data, the patients were informed about the remineralization treatment. Fluoride varnish was applied to the carious lesions at the baseline visit, and the patients were then reviewed after 1, 2, 3 and 4 weeks, with QLF assessment and fluoride varnish application repeated at each review. Repeated-measures ANOVA (alpha = 0.05) showed significant differences between Delta Q values at each visit (p < 0.001); Delta Q showed marked decreases at all the cut-off values (15, 20, 25, 30). The changes in Delta Q were not affected by the cut-off value. The Delta Q values of QLF showed differences at all visits. The QLF system was able to detect early root surface caries lesions in vivo. Bifluoride 12 varnish improved mineral levels as shown by the QLF system. The treatment response to chemicals of intact noncavitated root surface carious lesions could be followed nondestructively in the clinic using QLF to quantify remineralization at recall visits. Teeth with root surface caries can be kept by controlling their remineralization.
Keywords: Root surface intact caries lesion; OLF; Demineralization; Remineralization; Bifluoride 12; Clinic; INCIPIENT CARIES LESIONS; LASER FLUORESCENCE; MINERAL LOSS; ENAMEL LESIONS; IN-VITRO; QUANTIFICATION; QLF; PREVALENCE; DIAGNOSIS; MONITOR